Protection of personal data and “ECHR” - Mirko Klarić (Zbornik Radova Pravnog Fakulteta u Splitu, 2016)
Focus of this article is in protection of personal data as a elementary human right in scope of Convention for the Protection of Human Rights and Fundamental Freedoms. In article is also analysed regulations in Convention for the Protection individuals with regard to Automatic Processing of Personal Data Council of Europe, as a main legal act which regulate protection of personal data and right on individual on privacy. This Convention can be treated as lex specialis because create regulatory framework for one category of human rights: rights on privacy and protection of personal data. That category became more and more important because of highly technological development. In article is also presented regulatory framework related on personal data protection in five European countries: Croatia, Great Britain, France, Germany and Nederland. At the end of the article are presented empirical indicators which correlate with using of personal data. In concluding remarks has been described important role of personal data protection as a special type of protection of human rights in light of Convention for the Protection of Human Rights and Fundamental Freedoms.